Incorporating Stakeholder Thinking into the Neo-Classical Capital Circulation Model of the Firm - Näsi, Salme (Journal of business ethics, 2011)
This paper discusses and provides a tentative model of a firm for purposes of accounting. The paper first presents the neo-classical capital circulation model of the firm—a model that has been an integral part of Finnish business economics and accounting education for at least half a century. During the same period the stakeholder model has become an alternative model of the firm in Scandinavia. These models have represented two alternatives to define the firm in education. In this paper we try to combine these two models to provide a more comprehensive picture of the firm, especially from the accounting education perspective. An earlier version of this model was presented in 1995 in a book edited by Juha Näsi. Stakeholders with business transactions were seen to be crucial to firms and were categorized as primary in the 1995 model. In addition to stakeholders, a number of stakeholder issues were illustrated in the stakeholder model serving accounting as an educational framework. In this paper the earlier model has been updated, taking into account the current globalization and other developments in the business world.